Digital Legacies and Distressed Capacities - Khaliq Parkar (South Asia Multidisciplinary Academic Journal)
This paper shows how technology platforms affect the character and functioning of municipal governance. It does so by tracing the genesis, implementation, and effects of three technology platforms for spatial governance in Bhubaneswar. I show that these platforms are the result of the state of Odisha’s digitalization strategy, implemented alongside the widely discussed Smart Cities Mission. They are considered ICT-GIS platforms and leverage spatial and information technologies to monitor public lands, pinpoint households with alphanumeric codes, and algorithmically approve construction projects on private lands. I use interviews with state administrators, municipal staff, platform developers, and consultants, which shed light on the motivations for digitalizing existing governance processes, the early results of algorithmic governance, citizens’ use of digital tools, and the ways in which municipal capacities handle these transformations. The paper tries to identify digitalization’s role between technocratic solutionism and spatial surveillance in the governance of a city. I conclude that digital infrastructuring shifts control from weakened municipal departments to consultant-driven control over governance practices, and the three platforms limit access to democratic institutions.